"In Wales … we do things differently". The politics of asylum dispersal in the UK and emerging national (self-) imaginaries of hospitality in Wales. (May 2023) - Bernhardt, Franz
Abstract: The 1999 Immigration and Asylum Act marked a watershed moment for the politics of asylum in the UK, setting the discursive groundwork for the now infamous 'hostile environment'. This article is the first to compare the discursive framings of this formative act by the Home Office and UK government with those of the then newly devolved Welsh political institutions. While exploring the dominant visions of asylum as fear, unease and hostility marking the act, this paper highlights contrasting national narratives and imaginaries of welcome and hospitality in Welsh institutions. Drawing on a discourse analysis of archived policy documents, newspapers and interview material, the paper argues that these emerging hospitable imaginaries constituted a form of Welsh national identity formation against a less hospitable 'Other'- the UK sovereign state. This article contributes to the critical migration literature by questioning if the notion of hospitality involves more than the ambivalent framing of non-citizens as guests and others, or if instead it is more intended to differentiate from sovereign responses to asylum.